Strategy and business models - strange bedfellows? A case for convergence and its evolution into strategic architecture - G. M. Mansfield; L. C.H. Fourie (South African Journal of Business Management, 2004)
Strategy aims for sustainable competitive advantage; business models are said to be the sine qua non of value creation. Firms in the networked economy may ask which approach is the more relevant and whether either, or both, are sufficient for success - and then misinterpret the linkage between them. Internet-based businesses are faced with rapid change in an environment characterised by connectedness and choice in which dynamism, innovation and customer-centricity appear to be the winning ingredients for success. In the networked economy the internet with its open standards has created commercial arrangements which manifest a disdain for traditional boundaries and demand new patterns of management behaviour for effective performance. The classic approach to strategy formulation with its perceived indifference, for example, towards network formation, confusion around generic strategy deployment, lack of dynamism and its vacuous treatment of customer-centricity have led electronic business practitioners to the flawed conclusion that a business model is the only compelling strategic behaviour which predicates success. This conceptual paper builds a theoretical base which traces the roots of strategy and business models, reviews the context of each, postulates a relationship between these two fundamental approaches and offers some guidelines on the missing ingredients.
Keywords: 650